Characteristics of Tau Oligomers - Ren, Yan; Sahara, Naruhiko (Frontiers in Neurology, 2013)
In Alzheimer disease (AD) and other tauopathies, microtubule-associated protein tau becomes hyperphosphorylated, undergoes conformational changes, aggregates, eventually becoming neurofibrillary tangles (NFTs). As accumulating evidence suggests that NFTs themselves may not be toxic, attention is now turning toward the role of intermediate tau oligomers in AD pathophysiology. Sarkosyl extraction is a standard protocol for investigating insoluble tau aggregates in brains. There is a growing consensus that sarkosyl-insoluble tau correlates with the pathological features of tauopathy. While sarkosyl-insoluble tau from tauopathy brains has been well characterized as a pool of filamentous tau, other dimers, multimers, and granules of tau are much less well understood. There are protocols for identifying these tau oligomers. In this mini review, we discuss the characteristics of tau oligomers isolated via different methods and materials.